God, Creation and climate change: spiritual and ethical perspectives - Bloomquist, Karen L. (LWF studies, 2009)
Introduction (KB) - with 2008 council resolution at end 2008 survey, followed by the God, creation, and climate change resource -- "Human rights and climate change" (Martin-Schramm) -- Addressing realities on the ground (Bouka-Coula) -- Puri community -- Anapama : a faith and life changing experience -- Zachariah : "discerning the times : a spirituality of resistance and alternatives" -- Neuenfeldt : "caminhada : a pilgrimage with land, water and the Bible" -- Johnsen : "listen to the voice of nature". Indigenous perspectives -- Habel "wisdom cosmology and climate change" + "black saturday" hymn -- Rossing : God's lament for the earth : climate change, apocalypse, and the urgent Kairos moment -- Stuckelberger, "who dies first? : whom do we sacrifice first? : ethical aspects of climate justice" -- Moe-Lobeda "cross, resurrection, and the indwelling God" -- Bergmann: invoking the spirit amid dangerous environmental change